EFFECT OF PHOSPHATE FERTILIZATION AND SPRAYING WITH SEAWEED EXTRACT KELP 40 ON QUALITY, MINERAL CONTENT AND BACTERIAL NODULES IN TWO PEA CULTIVARS - Abdulraheem Mohammed; Marwa M. Hamdoon (Mesopotamia Journal of Agriculture)
This study was conducted in the vegetable farm/Hort. & land scape Dept./College of Agric. & Forestry / Mosul Univ. to study the effect of two levels of phosphate fertilization, zero, 40 kg P2O5/Donum, and spraying with three levels of seaweed extract, kelp 40, Zero, 2,4 ml/l in two pea cultivars namely: "Little Marvel and Fabreca". Plants were sprayed twice, the first one at 3-5 true leaf stage, whereas the second after 15 days from the first spraying. Results indicated that phosphate fertilization & seaweed extract showed a clearly effects in TSS, protein percentage of seeds, nitrogen & phosphorus concentrations of leaves, in addition to number of root nodules/plant. Phosphate treatment gave the highest protein percentage (30.08%), while spraying with 4 ml/l of seaweed extract resulted in the highest values of nitrogen, phosphorus concentrations in leaves, and the large number of root nodules/plant. The results revealed also that cultivars varied between them in all parameters studied.